Implementasi Administrasi Daily Light Vehicle Report (R1) dalam Mendukung Proses Otorisasi dan Penagihan Kendaraan Operasional di PT Wahanakarsa Swandiri - Cindy Raksandy Akbar; Okta Karneli (Yayasan Daarul Huda Kruengmane, 2026)
Operational vehicle usage reporting is an important part of corporate administration, particularly for companies that provide operational vehicle services to clients and require supporting documents for authorization and billing purposes. PT Wahanakarsa Swandiri has implemented the Daily Light Vehicle Report (R1) as a standard daily reporting format for light operational vehicle usage, compiled from trip detail data monitored by the Operation Control System (OCS) division. This community service activity was carried out through the Impactful Internship Program, focusing on mentorship in the preparation and verification of the R1 report, whose format was already established and had been in use prior to the activity. The activity followed the existing workflow, which included receiving vehicle trip detail data from the OCS division via email, printing the data according to vehicle unit codes, inputting trip information into the R1 format along with operational status coding (code 1 for working/on-location status, codes 2 and 3 for standby status, and code 4 for rest status), and submitting the report to the driver for the approval signature process from relevant parties. Once approved, the R1 report was forwarded to the Project Control division to serve as the basis for vehicle usage billing. The results show that the student's role in this process contributed to the accuracy and consistency of daily data entry, while also serving as a direct learning experience on how an administrative document functions as an authorization instrument and billing basis within the company's operational cycle. This activity strengthened students' understanding of applying Management Information System concepts and internal control, particularly transaction authorization, in real business administration practice.